PENGARUH PENGGUNAAN ALAT TANGKAP RAWAI DASAR (BOTTOM LONG LINE) PADA KEDALAMAN DAN WAKTU YANG BERBEDA TERHADAP HASIL TANGKAPAN DIPERAIRAN TELUK AWANG: The Effect Of Using Bottom Long Line Gear At Different Depths And Times On The Catch Results In The Waters Of Teluk Awang - Masturyadi, Masturyadi; Rizal, Lalu Samsul; Furkan, Al (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2025)
The purpose of this study was to determine the most effective water depth and the right time and the types of fish caught using bottom long line fishing gear (Bottom Long Line). This study was conducted in the waters of Teluk Awang, Central Lombok Regency. The method used in this study is the "experimental" method with a Randomized Block Design (RAK), with 3 (three) types of treatments consisting of 6 (six) variables and each treatment was repeated three times in the morning and evening so that 18 (eighteen) trips were obtained. The three treatments are different depths consisting of 15 meters, 20 meters and 25 meters. The results of the study showed that the highest catch was achieved by the P3 treatment at a depth of 25 meters carried out in the morning, as many as 19 fish weighing 25,986 grams, while the lowest catch was in the P1 treatment at a depth of 15 meters carried out in the afternoon, as many as 5 fish weighing 5,090 grams. Based on the Analysis of Variance (ANASRA) on the weight catch (grams) showed a significant difference where F hit. < F tab 5% (0.51 < 5.14).